Expression of genes encoding IGF1, IGF2, and IGFBPs in blood of obese adolescents with insulin resistance - Minchenko Dmytro O. (Sciendo, 2019)
Objective. The development of obesity and its metabolic complications is associated with dys-regulation of various intrinsic mechanisms, which control basic metabolic processes via changes in the expression of numerous regulatory genes. The main goal of this work was to study the association between the expression of insulin-like growth factors (IGF1 and IGF2) and IGF-binding proteins and insulin resistance in obese adolescents for evaluation of possible contribution of these genes in development of insulin resistance.